## Consider the following pair of equations: y = x + 4 y = −2x − 2 Explain how you will solve the pair of equations by substi

Question

Consider the following pair of equations:
y = x + 4
y = −2x − 2
Explain how you will solve the pair of equations by substitution. Show all the steps and write the solution in (x, y) form. There is no pic pls help xd

in progress 0
3 years 2021-08-04T09:50:21+00:00 1 Answers 200 views 0

x is equal to -2, and y is equal to 2.

Step-by-step explanation:

You can solve this type of question by solving one of the equations for a given variable, and substituting it into another.

Because both of these are definitions of y, we could simply say, y = y, and thus:

x + 4 = -2x – 2

3x = -6

x = -2

This tells us also that y, being equal to x + 4, must equal 2

We can find the same solution by solving one of them for x, then substituting that into the other.  We know:

y = x + 4

so we can also say:

x = y – 4

If we substitute that into the other:

y = -2x – 2

y = -2(y – 4) – 2

y = -2y + 8 -2

3y = 6

y = 2

which we can then plug into either of the original equations to solve for x:

y = x + 4

2 = x + 4

x = -2